Development of Youth Reforms in the Republic of Uzbekistan - Topildiev Odiljon Rakhimjonovich (International Journal on Integrated Education, 2022)
This article analyzes the development system of the state youth reform in the Republic of Uzbekistan, aimed at the harmonious upbringing of the younger generation, attention and care for young people, creating all the necessary conditions for them to take an independent step in life.